2022
DOI: 10.3389/fpls.2022.1038866
|View full text |Cite
|
Sign up to set email alerts
|

Opposite roles of MAPKKK17 and MAPKKK21 against Tetranychus urticae in Arabidopsis

Abstract: After recognizing a biotic stress, plants activate signalling pathways to fight against the attack. Typically, these signalling pathways involve the activation of phosphorylation cascades mediated by Mitogen-Activated Protein Kinases (MAPKs). In the Arabidopsis thaliana-Tetranychus urticae plant-herbivore model, several Arabidopsis MAP kinases are induced by the mite attack. In this study, we demonstrate the participation of the MEKK-like kinases MAPKKK17 and MAPKKK21. Leaf damage caused by the mite was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…In line with this, jasmonate-responsive genes were among the early responding genes including those that encode enzymes in volatile biosynthesis (i.e., AtTPS04/GES, AtCYP82G1 [ 49 , 50 ]), enzymes involved in sealing damaged tissue (i.e., AtPP2-A5 [ 51 ]), transcription factors (i.e., AtRRTF1, AtWRKY40, AtRAP2.6 [ 52 , 53 , 54 , 55 , 56 ]) and proteins involved in plant defense against pathogens or insects (i.e., AtTI6, AtMAPKKK21 [ 57 , 58 ]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with this, jasmonate-responsive genes were among the early responding genes including those that encode enzymes in volatile biosynthesis (i.e., AtTPS04/GES, AtCYP82G1 [ 49 , 50 ]), enzymes involved in sealing damaged tissue (i.e., AtPP2-A5 [ 51 ]), transcription factors (i.e., AtRRTF1, AtWRKY40, AtRAP2.6 [ 52 , 53 , 54 , 55 , 56 ]) and proteins involved in plant defense against pathogens or insects (i.e., AtTI6, AtMAPKKK21 [ 57 , 58 ]).…”
Section: Resultsmentioning
confidence: 99%
“…This likely reflects the expression of genes encoding enzymes in jasmonate biosynthesis (AtLOX2, At4CL8) and signaling (AtMYC2) that were more highly expressed in wounded WT compared with lox2 plants [ 4 ]. Jasmonate-responsive genes involved in plant resistance to insect herbivory, such as AtHPL/AtCYP74B2 , which encodes an enzyme involved in volatile biosynthesis [ 83 ], AtCLH1 , AtKTI3 , AtTI1 , AtARGAH2 and AtMAPKKK17 , reflect this pattern [ 58 , 84 , 85 , 86 ]. Genes involved in antioxidant pathways are upregulated in wounded WT plants, including those that encode proteins involved in the ascorbate/glutathione cycle (i.e., AtDHAR1 [ 87 ]) and anthocyanin biosynthesis (i.e., AtPAP1, AtTT8, AtGL3, AtTTG2, At4CL, AtTT7, AtDFR, AtLDOX, AtUF3GT, At1g14090, At3AT1, At3AT2, AtGSTF12, At5MAT [ 88 , 89 , 90 ]) ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heynh.) Columbia-0 (Col-0) accession were obtained from the Arabidopsis Biological Resource Center [ mkk3-1 (SALK_051970; Takahashi et al ., 2007), mkk3-2 (SALK_208528C; Sözen et al ., 2020), mpk1-1 (SALK_063847C; Enders et al ., 2017), mpk2-2 (SALK_047422C; Lv et al ., 2021), mpk7-1 (SALK_113631), mpk14-1 (SALK_022928C; Lv et al ., 2021), mapkkk13-1 (GK-277E09), map3k14-1 (GK-653B01; Sözen et al ., 2020), mapkkk15-1 (SALK_084817), map3k16 (Choi et al ., 2017), mapkkk17-2 (SALK_080309C; Romero-Hernandez and Martinez, 2022), mkkk18-2 (GK-676E02; Mitula et al ., 2015) and mapkkk20-3 (GK-458D07)]. Ds-transposon insertion lines of Arabidopsis Nossen accession were obtained from RIKEN BioResource Research Center [ mapkkk19-1 (pst14411) and mapkkk21-3 (psh20310)].…”
Section: Methodsmentioning
confidence: 99%
“…This suggested that the ABA pathway was activated; however, at 3 dpi, the PYL did not change, and the repressor PP2C was up-expressed, which resulted in MAPKKK (17)(18) being repressed (Figure 4; Table S9). MAPKKK17 was induced in response to a mite a ack in Arabidopsis [36], while MAPKKK18 (an ABA-activated kinase) was regulated by PP2C, which inhibited the kinase activity of MAPKKK18 [37]. The reduced transcription of MAPKKK18 in Arabidopsis exhibited obviously delayed leaf senescence [38].…”
Section: Signaling Molecule Responses To Pwn Infection Of P Thunbergiimentioning
confidence: 99%